2009
DOI: 10.1002/marc.200900387
|View full text |Cite
|
Sign up to set email alerts
|

Covalently Scaffolded Inter‐π‐System Orientations in π‐Conjugated Polymers and Small Molecule Models

Abstract: Organic π-conjugated polymers have emerged as one of the most fascinating classes of materials as they have found utility in a host of plastic electronics technologies. The distance between π-systems and their relative orientation dictate energy/charge transfer, conductivity, and photophysical properties of these materials in bulk. This Feature Article discusses π-conjugated polymers and model compounds in which specific inter-π-system interactions are covalently enforced and the effect that the scaffolding ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 50 publications
1
18
0
Order By: Relevance
“…This should be regarded as a transmolecular π-π conjugation 1 [23][24][25][26] which can reduce the triplet energy of Phe. Thus, Phe exists in the cocrystal as two states: an isolated state with π-holeÁ Á Áπ bonding between the 1,4-DBrTFB and Phe molecules in the columns and a delocalized state for Phe molecules located at inter-column positions, which may be significant in the modulation of luminescent behavior.…”
Section: Cocrystals By Pahs and Haloperfluorobenzenesmentioning
confidence: 99%
“…This should be regarded as a transmolecular π-π conjugation 1 [23][24][25][26] which can reduce the triplet energy of Phe. Thus, Phe exists in the cocrystal as two states: an isolated state with π-holeÁ Á Áπ bonding between the 1,4-DBrTFB and Phe molecules in the columns and a delocalized state for Phe molecules located at inter-column positions, which may be significant in the modulation of luminescent behavior.…”
Section: Cocrystals By Pahs and Haloperfluorobenzenesmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] The intriguing properties of π-conjugated materials can be controlled as a function of nanostructure and self-assembly process in supramolecular assemblies. For the construction of nanostructured materials, the self-assembly of small molecules into supramolecular polymers has been widely adopted.…”
Section: Introductionmentioning
confidence: 99%
“…Theoretical studies have suggested that a face‐to‐face π‐stacking interaction with a plane‐to‐plane distance of 3.2–4.0 Å is ideal for facilitating charge mobility through a CP film . Some investigators have sought to alleviate the complication of inter‐π‐system interaction influences on polymer properties by appending the polymers with sterically encumbered substituents to prevent close contacts between polymer chains .…”
Section: Introductionmentioning
confidence: 99%
“…Some investigators have sought to alleviate the complication of inter‐π‐system interaction influences on polymer properties by appending the polymers with sterically encumbered substituents to prevent close contacts between polymer chains . Other researchers have devised molecular scaffolding and covalent crosslinking strategies to constrain adjacent polymer chains in near‐ideal orientations to improving charge/energy transport through a material . Two of the scaffolding most relevant to the current work are the [2.2]paracyclophane (i.e., in P3 , Figure B) and the oxacyclophane (i.e., in M5 , M6 , CyM , and CyP , Figure ) scaffolding units.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation